Report on Workshop: Refugee Resettlement and Education in New England - Raven Roberts, Angela (Tufts Archival Research Center, 2005)
The objective of the meeting was to host a two-day meeting to discuss the educational and social needs of refugee youth being re-settled in the Boston area. Participants were invited from a number of resettlement and refugee welfare agencies in the Boston and Portland regions as well as teachers, youth workers, volunteers and representatives from refugee community organizations. In addition we were joined by representatives of refugee sending organizations in East Africa. Key highlights of the meeting included the active participation of and presentations by a number of youth from the Boston and Portland area.